Internal and external generalizability of temporal dose-response relationships for xerostomia following IMRT for head and neck cancer - Thor, Maria (Radiother Oncol, 2016)
BACKGROUND AND PURPOSE: To study internal and external generalizability of temporal dose-response relationships for xerostomia after intensity-modulated radiotherapy (IMRT) for head and neck cancer, and to investigate potential amendments of the QUANTEC guidelines. MATERIAL AND METHODS: Objective xerostomia was assessed in 121 patients (n(Cohort1)=55; n(Cohort2)=66) treated to 70Gy@2Gy in 2006–2015. Univariate and multivariate analyses (UVA, MVA with 1000 bootstrap populations) were conducted in Cohort1, and generalizability of the best-performing MVA model was investigated in Cohort2 (performance: AUC, p-values, and Hosmer-Lemeshow p-values (p(HL))). Ultimately and for clinical guidance, minimum mean dose thresholds to the contralateral and the ipsilateral parotid glands (Dmean(contra), Dmean(ipsi)) were estimated from the generated dose-response curves. RESULTS: The observed xerostomia rate was 38%/47% (3 months) and 19%/23% (11–12 months) in Cohort1/Cohort2. Risk of xerostomia at 3 months increased for higher Dmean(contra) and Dmean(ipsi) (Cohort1: 0.17•Dmean(contra)+0.11•Dmean(ipsi)−8.13; AUC=0.90±0.05; p=0.0002±0.002; p(HL)=0.22±0.23; Cohort2: AUC=0.81; p<0.0001; p(HL)=0.27). The identified minimum Dmean(contra) thresholds were lower than in the QUANTEC guidelines (Cohort1/Cohort2: Dmean(contra)=12/19 Gy; Dmean(contra), Dmean(ipsi)=16, 25/20, 26 Gy). CONCLUSIONS: Increased Dmean(contra) and Dmean(ipsi) explain short-term xerostomia following IMRT. Our results also suggest decreasing Dmean(contra) to below 20 Gy, while keeping Dmean(ipsi) to around 25 Gy. Long-term xerostomia was less frequent, and no dose-response relationship was established for this follow-up time.